OPTIMALISASI MANAJEMEN RESIKO DALAM PENGADAAN SARANA DAN PRASARANA PENDIDIKAN DI SMP INTAN AL-SALI - Daulay, Saiful Ma'arif; Hidayat, Wahyu (Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to analyze the optimization of risk management in efforts to procure facilities and infrastructure to improve the quality of education at Intan Al-Sani Junior High School. Risk management has become an important topic in various sectors, including in the education sector. In the context of education, risk management is concerned with identifying, evaluating, and controlling risks that can affect the achievement of educational goals. This research uses descriptive analysis methods and literature reviews to collect relevant data and information about risk management in the procurement of educational facilities and infrastructure. The results of this study show that the effective implementation of risk management can make positive optimization in the procurement of educational facilities and infrastructure. The optimization includes increasing the security of educational facilities and infrastructure, reviewing priorities in the procurement of educational facilities and infrastructure, and more effective strategic planning. However, challenges faced in implementing risk management in education also need to be overcome, such as limited resources, resistance to change and the complexity of the educational environment. This research contributes to the understanding of risk management in the procurement of educational facilities and infrastructure and provides recommendations for educational practitioners and decision-makers to improve the quality of education through an effective risk management approach.